1978
DOI: 10.1038/272798a0
|View full text |Cite
|
Sign up to set email alerts
|

Why do nucleic acids have 3′5′ phosphodiester bonds?

Abstract: Details of the stereochemistry of the 2'5' and 3'5' dinucleoside monophosphates of polynucleotides have been delineated in aqueous solution using nuclear magnetic resonance spectroscopy. Incorporation of these experimentally determined geometries into the structure of polynucleotides reveals that the intrinsic spatial configurations of the 2'5' bonds cannot support helical structures whereas the geometries of 3'5' bonds allow the formation of helical configurations for RNA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

1980
1980
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(25 citation statements)
references
References 23 publications
3
22
0
Order By: Relevance
“…Those for A2'-5'U (5.6 mM) are from 360-MHz spectra, those for A2'-5'A (7.4 mM) from 100-MHz spectra It is therefore concluded that the SN stack makes up the far greater part of the stacked state in A2'-5'U at low temperature. This finding is in agreement with NMR studies on A2'-5'C and G2'-5'U [9,32] which revealed a preference for the S conformation in the purine (R) fragment and a preference for the N conformation in the pyrimidine (Y) fragment in R2'-5'Y dinucleotides. The difference between A2'-5'U and A2'-5'A is also seen in the different temperature dependency of the CD spectra.…”
Section: The Conformation Of A2'-5'usupporting
confidence: 81%
See 1 more Smart Citation
“…Those for A2'-5'U (5.6 mM) are from 360-MHz spectra, those for A2'-5'A (7.4 mM) from 100-MHz spectra It is therefore concluded that the SN stack makes up the far greater part of the stacked state in A2'-5'U at low temperature. This finding is in agreement with NMR studies on A2'-5'C and G2'-5'U [9,32] which revealed a preference for the S conformation in the purine (R) fragment and a preference for the N conformation in the pyrimidine (Y) fragment in R2'-5'Y dinucleotides. The difference between A2'-5'U and A2'-5'A is also seen in the different temperature dependency of the CD spectra.…”
Section: The Conformation Of A2'-5'usupporting
confidence: 81%
“…Second, the A(l) and U(2) ribose rings in the crystal structure of A2'-5'U have the S and N conformation respectively, whereas the interplanar base-base distance equals 0.34 nm. Third, a possible 'mixed' SN conformation is also reflected in the NMR 1 '2'-coupling constants of A2'-5'U, G2'-5'U and A2'-5'C [9,32], This simple statistical 'mixed' stack model cannot be used in the case of A2'-5'A2'-5'A. In this molecule partly stacked states may also be present, e.g.…”
Section: Stackingmentioning
confidence: 99%
“…2',5"-Linked DNA (21)(22)(23)(24)(25)(26)(27), and there is as well some experimental evidence (28) on the kinetic lability of a normal 3',5" oligonucleotide containing one 2',5" linkage. We have now addressed the properties of two classes of materials: (i) DNA oligonucleotides containing one or two 2',5" linkages in addition to the normal links, and (ii) oligonucleotides with only 2',5" linkages, built up from 3-deoxynucleosides.…”
Section: Cleavage Of Rna By Imidazole and Other Buffersmentioning
confidence: 99%
“…Although NMR structures of a homogeneously 2′-5′-linked DNA and RNA duplex as well as X-ray crystal structures of 2′-5′-linked dinucleotides have been reported (19)(20)(21)(22)(23)(24)(25)(26), no crystallographic data are available on mixed-backbone RNA. Here we report high-resolution crystal structures of three RNA 10mer duplexes of the same self-complementary sequence, the first being native RNA, the second containing two, and the third containing six 2′-5′ linkages.…”
mentioning
confidence: 99%